Introduksi Lipstik Cair dari Umbi Buah Bit (Beta vulgaris L.) di Pasantren Putri - Miksusanti Miksusanti; Azhar Kholiq; Aldes Lesbani; Endri Junaidi; Risfidian Mohadi; Neza Rahayu; Desnelli Desnelli; Syaflina Lamin (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
A community service scheme for implementing science and technology has been carried out from Srwiijaya University funding sources. Community service is carried out at the Ittifaqiah Islamic Boarding School for women in Indralaya, Ogan Ilir, South Sumatra. Participants who attended were 60 Islamic boarding school students in the science class, 10 science teachers and 2 Ittifaqiah administrators. Community service was carried out using lecture methods and demonstrations of making liquid lipstick in front of female students and teachers. The natural ingredients used in making lipstick in this service activity are beet root extract, virgin coconat oil (VCO), soy lecithin, gum Arabic, food flavors and food preservatives. There were 20 organoleptic tests carried out on Unsri female students on the liquid lipstick made in this service activity. Fifteen people said they really liked it, 3 people said they liked it quite a lot and 2 people said they liked the product a little. The survey on the results of service activities showed that 50 female students said they really understood how to make liquid lipstick, 8 students said they understood quite well how to make liquid lipstick with the red color of beetroot and 2 female students said they understood a little.